BIOGRAFI AHCMAD GUSNUR WIRAUSAHA HOME INDUSTRY KERUPUK JANGEK DINAGARI MUARO PANEH TAHUN 2006-2022 - Shalina, Shalina; Naldi, Hendra (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This research is in the form of a thematic biographical research about the life journey of Achmad Gusnur, a jangek cracker home industry entrepreneur who is in Nagari Muaro Paneh, Solok district.The purpose of this study was to find out what and how Ahcmad Gusnur's strategy was in starting a jangek karupuk business in Nagari Muaro Paneh, Bukit Sundi Solok sub-district. This research is qualitative because it uses historical methods consisting of heuristics, criticism, interpretation, and historiography. This jangek cracker business was started in 2006 which was started by the owner, because the owner saw that the jangek cracker business was minimal in the area where it was located, while the raw materials were easy to obtain, but in starting this business the owner did not have intelligence about the business he was running, thanks to his determination and courage. taking the risk of the owner studying for 6 months to Batu Sangkar to increase knowledge about jangek crackers and he is also able to learn automatically with the intelligence he has. Keywords: Biography, Entrepreneur, Home industry, jangek crackers